MOTIVASI SISWA TERHADAP PEMBELAJARAN TARI DI SMP NEGERI 2 PADANG - Monalisa Monalisa; Yuliasma Yuliasma; Afifah Asriati (FBS Universitas Negeri Padang, 2013)
Abstract This article aimed at determining students’ motivation in learning dancing at SMP Negeri 2 Padang. This research focused on factors which caused students’ low motivation to follow the dance lesson at SMP Negeri 2 Padang. The design of this research was the descriptive qualitative reseach. The object of the research was students’ motivation in learning dancing at SMP Negeri 2 Padang. The data were obtained from observation, interview, and literature review. The information was gotten from the art teachers as well as students of SMP Negeri 2 Padang. The primary instrument in is research was the researcher herself while the secondary instruments were observation notes, recordings, and videos. The data were analyzed by using the phenomenology technigue. Based on the data analysis, it was found that students’ low motivation was due to the intrinsic and extrinsic factors from within themselves supported by the teachers’ performances such as the learning method and media used which could not improve students’ motivation. Keywords: Learning Dancing, Students’ Low Motivation